Unveiling ferroptosis genes and inhibitors in diabetic retinopathy through single-cell analysis and docking simulations - Md. Maqsood Ahamad Khan; Ananya Ganguly; Shubhrajit Barman; Chirasmita Das; Senthil Kumar Ganesan (Biochemistry and Biophysics Reports)
Diabetic retinopathy (DR) is a common microvascular complication of diabetes and a leading cause of vision loss worldwide. Although several mechanisms have been implicated in the pathogenesis of DR, emerging evidence suggests a link between ferroptosis and DR. Unfortunately, the exact mechanism underlying this connection is not clear. Therefore, investigating the role of ferroptosis in diabetic retinopathy holds promise for advancing our understanding of this complex disease and developing innovative treatments. We have identified differentially expressed genes (DEGs) and differentially expressed marker genes (DEMGs) from open-source single-cell RNA sequencing datasets by using in depth in silico approach. Subsequently, ferroptosis-associated DEGs (FA-DEGs), ferroptosis-associated DEMGs (FA-DEMGs), and ferroptosis-associated Hub Genes (FAHGs) were identified. The FDA-approved drugs for our target proteins were also identified, and their ADMET properties were assessed. Molecular docking and simulation were utilized to explore the interaction stability of the compounds with the target proteins. Overall, we identified 63 FA-DEMGs that were significantly enriched in Peroxiredoxin activity, Ferroptosis, Mitophagy, and Autophagy. Further analysis predicted that PRDX1 and UBC are candidate target proteins. Molecular docking results showed that dexamethasone has a high binding affinity for both PRDX1 and UBC. Additionally, molecular dynamics simulations revealed that dexamethasone (which showed the best hit in the docking analysis) exhibited a ‘stable effect’ on both PRDX1 and UBC. To summarize, this study showed that PRDX1 and UBC could be suitable therapeutic targets for dexamethasone, which might be helpful in the advance of DR treatments in the future.